Using 'voice' to understand what college students with intellectual disabilities say about the teaching and learning process. Issue 1 (29th January 2015) - Kubiak, John
Abstract : There is a growing awareness of the value of using pupils' voices in educational research. At primary and second level, the principle of pupil voice has gained in profile over the last decade. However, in higher education, the use of voice in research collaborations remains under‐theorised and under‐utilised. This paper reports on an inclusive phenomenographic study undertaken with college students with intellectual disabilities (ID). It outlines how pupil voice can be used to gain a deeper understanding of the teaching and learning process. The strategies that promoted learner engagement and autonomy include establishing a supportive learning climate or environment, and promoting self‐regulated learning strategies. These findings suggest that the use of pupil voice is fundamental to changing the way teachers think about students with ID and their learning.